Growth of Enterobacter cloacae in the presence of 25% sodium dodecyl sulfate. - Kramer, V C (1980)
The growth of Enterobacter cloacae in 25% sodium dodecyl sulfate is described. The bacteria appeared to tolerate sodium dodecyl sulfate rather than metabolize it. The process was energy dependent, and cell lysis occurred during stationary phase. Extreme detergent resistance may be characteristic of the genus Enterobacter.